(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This study analyzed the effect of caregiver’s gender (mother/father) and infant's gestational age (preterm/term) on caregiver-infant interaction. Eleven mother-infant dyads and 18 father- infant dyads participated, observed for five minutes. The behaviors of the caregiver and of the infant were analyzed by Interadíade. Two-way ANOVAs showed significant differences for intrusiveness [F(1, 25) = 8.659; p = 0.007)]. Mothers of full-term infants were more intrusive when interacting with their infant compared to fathers of full-term infants (p=0.004) and mothers of preterm infants (p=0.010). No effects on the infant's behaviors were found. The results suggest that families may benefit from intervention focused on the promotion of responsiveness.